Stagnation flow of eyring-powell hybrid Cu-Al2o3/water nanofluid towards a riga plate with newtonian heating - Aljabali, Ahlam; Abdul Rahman, Mohd Kasim; Najiyah Safwa, Khashi’ie; Iskandar, Waini; Noor Amalina Nisa, Ariffin (Shahid Chamran University of Ahvaz, 2024)
The problem of convective heat transfers of Eyring-Powell conveying Copper (Cu) coupled with alumina (Al2O3) are employed as the combination of particles, along with water as the base fluid over a vertical Riga plate is numerically addressed. The performance of heat transmission is influenced by the electromagnetohydrodynamic (EMHD) imposed produced from the Riga plate, and it could be used to postpone boundary layer separation. A model in the form of Partial Differential Equations (PDEs) is introduced to describe the physical behavior of the proposed problem. With the inclusion of relevant equation variables, this collection of PDEs is transformed into Ordinary Differential Equations (ODEs) which are in a less complex form. Then the bvp4c solver was employed to solve the respective equations. The characteristics of fluid velocity and temperature are investigated graphically. It is found the buoyancy assisting and opposing flows offered dual solutions whereas the purely forced convection flow gives a unique solution. Through an investigation of flow stability, the first solution is confirmed as the physical one. In essence, the volumetric concentration of Cu increases the heat-transferring ability for assisting and opposing flows. The higher suction imposed at the boundary causes a decrease in the heat transfer rate under the shrinking case.